Effectiveness of Individualised Homoeopathic Medicines versus Conventional Treatment in the Management of Primary Dysmenorrhoea in Young Unmarried Females: A Randomised, Open-Label, Clinical Study - Jain, Lily; Nayak, C.; Sharma, M. B.; Gehlot, Kushal (Homœopathic Links, 2020)
Background Primary dysmenorrhoea (PD) is painful menstruation without any identifiable pelvic pathology. More than 70% of teenagers suffer from varying degrees of discomfort during menstruation. Effective conventional treatment of PD includes non-steroidal anti-inflammatory drugs or oral contraceptive pills that usually have adverse effects.Objective The objective of the present study was to compare the effectiveness of individualised homoeopathic medicines with symptomatic conventional treatment in management of PD in young unmarried females by using Visual Analogue Scale (VAS) for assessing intensity of pain and World Health Organization Quality of Life: Brief Version (WHOQOL-BREF) scale for assessing the quality of life (QoL).Materials and Methods In this randomised, open-label, clinical study, 80 patients were randomly allocated in two groups: one with indicated homoeopathic medicines (Group I; N = 40) and the other with conventional treatment (Group II; N = 40). The selection of homoeopathic medicines was based on individualisation, and follow-up of cases was done every month for six cycles. VAS score was used to assess pain intensity and WHOQOL-BREF scale was used for assessing QoL, at 3 and 6 months of treatment.Results In Group I, out of 40 patients, 14 (35%) cases reported moderate pain and 26 (65%) reported severe pain before treatment, out of whom 29 (72.5%) patients had mild pain, 8 (20%) cases moderate pain and 3 (7.5%) cases severe pain, after homoeopathic treatment. In Group II, out of 40 patients, 11 (27.5%) reported moderate pain and 29 (72.5%) had severe pain before treatment, whereas 12 (30%) patients reported mild, 16 (40%) moderate pain and 12 (30%) severe pain, after conventional treatment. The t-value was –4.186 (p < 0.0001) for VAS and 3.988 (p < 0.0001) for overall domain WHOQOL-BREF mean transformed score.Conclusion It was concluded that intensity of pain during menses was reduced and QoL improved in patients with PD in homoeopathic intervention group, which proved the effectiveness of individualised homoeopathic medicines.
Keywords: primary dysmenorrhoea; individualised homoeopathic medicines; conventional treatment; WHOQOL-BREF; Visual Analogue Scale (VAS)